Assessing risk in times of climate change and COVID-19: city region food system of Tamale, Ghana - Food and Agriculture Organization of the United Nations; RUAF Foundation; International Water Management Institute (Food and Agriculture Organization of the United Nations, 2021)
This factsheet provides information on the general knowledge collected by the city region food system (CRFS) project in its phase 2 regarding the assessment of risks for the CRFS of Tamale. The data was collected through literature review and stakeholder consultations.